2008
DOI: 10.1007/s11910-008-0024-z
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal seizures and the effects of anticonvulsants on sleep

Abstract: Epilepsy is a common condition that affects up to 1% of the population. Patients with epilepsy are particularly sensitive to the adverse effects of sleep disruption. Failure to recognize and treat sleep disturbances can lead to worsening of attention, cognitive functioning, and quality of life, and can increase seizures. Anticonvulsant agents have the potential to either improve or worsen sleep and sleep disorders in patients with epilepsy. Therefore, awareness of the implications of sleep disorders and antico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…23 Successful treatment of nocturnal seizures will improve sleep and reduce daytime sleepiness in children with Dravet syndrome. In our cohort, 20 children (35%) had sleep-wake transition disorders, with 54% of children younger than 5 years old affected.…”
Section: Discussionmentioning
confidence: 99%
“…23 Successful treatment of nocturnal seizures will improve sleep and reduce daytime sleepiness in children with Dravet syndrome. In our cohort, 20 children (35%) had sleep-wake transition disorders, with 54% of children younger than 5 years old affected.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that in some epilepsies, certain normal states of vigilance are more conducive to seizure than others34,35,36. Seizure recurrence is also correlated with physiological rhythms24,37 and drug taper38.…”
Section: Clinical Aspects Of Epilepsy and Objectives For Electrothmentioning
confidence: 99%
“…Confounding factors: Drug taper38, physiological rhythms37, sleep stage34, stress, and various other factors are known to influence seizure rate and/or severity, and thereby interfere with the quantitative assessment of treatment effects.…”
Section: Clinical Aspects Of Epilepsy and Objectives For Electrothmentioning
confidence: 99%
“…Among them, sleep apnea, agrypnia and daytime drowsiness are some of the most common causes of dyssomnia (16). Among the common population, the incidence rate of sleep apnea is at least 3%, while polysomnography analysis of investigated epileptic patients revealed that the incidence rate of sleep apnea may be up to 70%.…”
Section: Discussionmentioning
confidence: 99%